Demonstration of Streptococcus mutans with a Cell Wall Polysaccharide Specific to a New Serotype, k, in the Human Oral Cavity - Nakano, Kazuhiko (American Society for Microbiology, 2004)
Streptococcus mutans organisms are occasionally isolated from the blood of patients with infective endocarditis, though the mechanisms of invasion and survival remain to be elucidated. Two of four blood isolates from patients with bacteremia or infective endocarditis (strains TW295 and TW871) were serologically untypeable by immunodiffusion testing, which was due to a lack of the glucose side chain of the serotype-specific polysaccharide antigen of S. mutans. Immunodiffusion analyses using antisera against these strains demonstrated that 2 of 100 isolates from 100 subjects showed a positive reaction, while further analysis of 2,500 isolates from 50 subjects revealed that all 50 isolates from a single subject were not reactive with anti-c, -e, and -f antisera, though they were reactive with anti-TW295 and -TW871 antisera. The oral isolates showed biological properties similar to those of the reference S. mutans strain MT8148, including high levels of sucrose-dependent adhesion and cellular hydrophobicity, along with expression of glucosyltransferases and a protein antigen, PA. We designated these organisms serotype k. A glucose side chain-defective mutant strain was then constructed by insertional inactivation of the gluA gene of strain MT8148, which showed biological properties similar to those of serotype k of S. mutans. Serotype k oral isolates were less susceptible to phagocytosis, as were the gluA-inactivated mutant of strain MT8148 and blood isolates. These results indicate that S. mutans serotype k strains are present in the oral cavity in humans and may be able to survive longer in blood owing to their low susceptibility to phagocytosis.